Education in the East, Emigrating to the West? - d'Artis Kancs; Julda Kielyte (Economics and Econometrics Research Institute (EERI), 2010)
This paper examines the potential impacts of East-West migration of talents on the innovative capital and hence the long-run growth prospects in Eastern sending countries. Complementing previous studies, we examine the impact of high skill migration not only on the formation of human capital, but also consider migration's impact on knowledge capital in the sending countries. In line with previous studies we find that in the short- to medium-term high skill migration strictly reduces national innovative capital and hence increases the gap between East and West. However, these effects might be mitigated by factors such as reinforced education of workers, productive investment of remittances, return migration and increased knowledge transfer. Given that the emigration of highly skilled affects human capital differently than knowledge capital, addressing the adverse impacts of the most talented and highly skilled worker emigration efficiently, differentiated policies are required for human capital and knowledge capital.
Keywords: D50; D80; F22; F24; H52; I21; J24; J61; O15; 330; International labour migration; skilled workers; growth; human capital